2019
DOI: 10.1002/pros.23823
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2‐ERG fusions linked to prostate cancer racial health disparities: A focus on Africa

Abstract: Background The androgen‐regulated gene TMPRSS2 to the ETS transcription factor gene ERG fusion is the most common genomic alteration acquired during prostate tumorigenesis and biased toward men of European ancestry. In contrast, African American men present with more advanced disease, yet their tumors are less likely to acquire TMPRSS2‐ERG . Data for Africa is scarce. Methods RNA was made a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 20 publications
4
32
1
Order By: Relevance
“…Indeed, ERG expression was identified to be a promising biomarker for PCa detection and prognosis . We found that the frequency of expression of ERG was lower in our African Caribbean population (26.6%) than in our Metropolitan French population (43.1%), which is similar to the literature among African descendants and Caucasians . Moreover, we found that ERG expression was associated with lower grade groups and was a negative predictor of high‐grade groups in our African Caribbean population.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Indeed, ERG expression was identified to be a promising biomarker for PCa detection and prognosis . We found that the frequency of expression of ERG was lower in our African Caribbean population (26.6%) than in our Metropolitan French population (43.1%), which is similar to the literature among African descendants and Caucasians . Moreover, we found that ERG expression was associated with lower grade groups and was a negative predictor of high‐grade groups in our African Caribbean population.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we found that ERG expression was associated with lower grade groups and was a negative predictor of high‐grade groups in our African Caribbean population. Similarly, in African descent populations, Blackburn et al found that ERG expression was related to low‐grade disease in young patients, and Taris et al demonstrated that ERG expression was associated with longer survival in patients with both localized and castration resistance PCa. ERG expression at diagnosis might give important prognostic information, as it seems to be inversely associated with aggressive PCa in African descent men.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They observed that black men have an increased risk of transformation to clinically significant cancer compared to white men. Blackburn and his colleagues (20) tried to investigate the association between the underlying genetic differences for prostate cancer with the racial variations among peoples. They reported a lower frequency for TMPRSS2-ERG fusion which is inversely associated with aggressive prostate cancer in black South Africans males compared to those from European ancestry.…”
Section: Prostate Cancermentioning
confidence: 99%
“…A possible explanation could be the autoregulatory effect of AR on its own promoter [ 37 ]. In order to measure AR activity in KDM7A knock-down cells, the expression of previously reported downstream target genes of AR was screened using RT-qPCR [ 38 , 39 , 40 , 41 , 42 , 43 ]. The relative mRNA levels of these genes, compared with those of LNCaP, are listed in Supplemental Figure S1C .…”
Section: Resultsmentioning
confidence: 99%